A 1998 Social Accounting Matrix for Thailand - Li, Jennifer Chung-I (International Food Policy Research Institute, 2002)
This paper documents the features of a 1998 social accounting matrix (SAM) for Thailand. It begins with a description of the overall economy both via a macro SAM and a national accounts balance sheet. The macro SAM was the result of aggregating a micro SAM; a mapping of the final micro SAM to the macro SAM is presented. The micro SAM was a modified version of a SAM obtained from the Thai Development Research Institute (TDRI). The paper describes the modification process in detail. The original dataset obtained from TDRI was a "balanced™ matrix." The converted SAM, after the modification, was still balanced. It was therefore unnecessary to apply any balancing procedure. The final 1998 micro SAM for Thailand has 61 sectors, 3 household types, and 3 factors (labor, agricultural capital, and non-agricultural capital). Particularly helpful for the intended analysis on energy and environmental policy is that it has 8 primary energy sectors, 5 transportation sectors, and a health and medical treatment commodity account.